The Influence Of Entrepreneurial Practice Learning On Entrepreneurial Activities And Formation Of Character - Mispandi, Mispandi; Fahrurrozi, Muh (IJE : Interdisciplinary Journal of Education, 2024)
The Influence of Learning Entrepreneurship Practices on Entrepreneurial Activities and Character Formation. This research aims to determine: 1) the influence of learning entrepreneurial practices on student activities. 2) entrepreneurial practice learning methods for the formation of students' entrepreneurial character. This type of research is quantitative with an ex post facto research design. The population in this study were students in classes X1 and X2 at SMKN 1 Sambelia. This research did not use a sample but used a population as the research object with a population of 48 students. The data analysis technique used is simple regression analysis. The results of this research show that: 1) There is a significant influence of the entrepreneurial practice learning method on student activities, in this case shown by the calculated t value of (3.711) > t table (1.717). 2) There is a significant influence of the entrepreneurial practice learning method on the formation of This entrepreneurial character of students is shown by the calculated t value (4.737) > t table (1.717).